Mens Rea and Ultimum Remedium in Distinguishing Breach of Contract from Fraud: Analysis of Indonesian Supreme Court Decision No. 4/Yur/Pid/2018 - Chandi Aulia; Amanda Adelina Harun; Nurifana Umar; Ahmad Ridhwan Abd Rani (al-Battar: Jurnal Pamungkas Hukum, 2026)
The intersection between breach of contract (wanprestasi) and the criminal offense of fraud in contractual relationships creates legal issues in determining the boundary between civil and criminal liability. Previous studies generally discuss elements of fraud, breach of contract, and the principle of good faith separately, resulting in a lack of research that specifically analyzes Supreme Court Decision Number 4/Yur/Pid/2018 by integrating the perspectives of mens rea, the principle of good faith, and civil liability. This study aims to analyze the juridical construction employed by the Supreme Court in distinguishing breach of contract from fraud and to examine civil liability arising from breach of contract containing elements of fraud. This study is normative legal research using statutory, case, and conceptual approaches. The novelty of this study lies in the application of the perspectives of mens rea and the principle of ultimum remedium as instruments to limit the criminalization of contractual disputes in analyzing Supreme Court Decision Number 4/Yur/Pid/2018. The findings show that the existence of mens rea from the initial formation of the agreement serves as the main parameter in distinguishing breach of contract from fraud, while contractual violations without malicious intent remain within the scope of civil law, with remedies in the form of specific performance, compensation, or contract termination. This study also finds that the decision has not provided detailed parameters regarding the limits of mens rea and the principle of good faith, which may lead to differing interpretations in judicial practice. Therefore, further development of jurisprudence and legal doctrine is required to strengthen legal certainty in the settlement of contractual disputes.